Organochlorine pesticide levels in maternal blood and placental tissue with reference to preterm birth: a recent trend in North Indian population - Tyagi, Vipin; Garg, Neha; Mustafa, M. D.; Banerjee, B. D.; Guleria, Kiran (Environmental monitoring and assessment, 2015)
Organochlorine pesticides (OCPs) have been widely used in public health and agriculture programs in developed as well as developing countries, including India. Being xenoestrogenic in nature, OCPs may act as endocrine disruptors leading to preterm birth (PTB) through disturbance of normal estrogen-progesterone ratio. PTB is the leading cause of neonatal deaths worldwide. Therefore, the present study is aimed to determine the extent to which persistent environmental chemicals may accumulate in pregnant women and placenta and ascertain possible associations between exposure level and period of gestation (POG), baby weight, and/or placental weight in PTB cases. Maternal blood and placenta samples of PTB cases ( n = 50) and subjects of term delivery as controls ( n = 50) were collected. OCP residue levels were estimated by the gas chromatography system equipped with an electron capture detector. Significantly higher levels of α-hexachlorocyclohexane (α-HCH), β-hexachlorocyclohexane (β-HCH), dichlorodiphenyldichloroethane (DDD), and dichlorodiphenyldichloroethylene (DDE) were found in maternal blood of PTB cases as compared to control. Significantly higher levels of DDE and dichlorodiphenyltrichloroethane (DDT) were also found in placental tissue of PTB cases as compared to control group. There was a statistically significant negative correlation between maternal blood level of α-HCH and birth-weight ( r = −0.299) and POG ( r = −0.234). γ-Hexachlorocyclohexane (γ-HCH) and dieldrin had a negative correlation with placental weight ( r = −0.401 and −0.256, respectively), and DDE and β-HCH had a negative correlation with POG ( r = −0.251 and −0.229, respectively). The presence of OCPs in maternal blood and placental tissue represents prenatal exposure hazard for fetuses due to chronic bioaccumulation and poor elimination with possible deleterious effect on health.